New psychometric evidences on the Dental Environment Stress questionnaire among Romanian students - Ruxandra Sfeatcu; Beatrice Adriana Balgiu; Ioanina Parlatescu (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The academic environment is a challenge for dental students due to the multiple sources of stress they face. For this reason, the present study analyzes the psychometric properties of the Dental Environment Stress (DES) questionnaire. The secondary objective was to identify the specific sources of stress perceived by dental students related to gender and years of study. MATERIALS AND METHODS: A cross-sectional study was conducted among dental students (n = 340; Mage = 22.45) from the Romanian University of Medicine and Pharmacy in October- December 2019. The factorial structure of the questionnaire was performed by means of the confirmatory factor analysis (CFA) and the multi group-CFA. The convergent and divergent validities were measured by associating DES with scales that measure depression, anxiety, and tension/stress (Depression Anxiety Stress Scale-21-R), perceived stress (Perceived Stress Scale-14), and life satisfaction (Satisfaction with Life Scale). RESULTS: New measure obtained supported a five-factor and thirty-item structure, which is gender invariant. All the factors within DES have a significant positive correlation with depression, anxiety, tension/stress, and perceived stress and a negative correlation with life satisfaction. The Cronbach's α coefficients are acceptable (range: 0.67-0.89). The female students perceive aspects related to performance, the relations with the faculty, clinical responsibilities, and personal life to be more stressful than males. Senior students perceive more stressed aspects related to personal life, while freshmen have higher scores on stress associated with clinical responsibilities. CONCLUSIONS: The present results show that DES has psychometric properties which are adequate for the assessment of dental stress in the case of Romanian students; nevertheless, it is necessary to extend the use of DES to students attending other universities and to dental practitioners.